EFFECT OF PRELOAD OF ANGULAR CONTACT BALL BEARINGS ON LIFE OF BEARINGS - Andrzej RACZYŃSKI; Jarosław KACZOR (Scientific Journal of Silesian University of Technology. Series Transport)
Angular contact ball bearings are commonly used in such situations when you need to reach high bearing stiffness. However, a significant stiffness increase can be achieved only through the introduction of preload to the angular contact bearings. The purpose of this paper is to present a method for assessing the effect of preload of the angular contact bearings for their durability.